The Effect of Education on Writing Integrated Patient Progress Notes (IPPNs) at Several Government Hospitals in Bukittinggi, Indonesia - Serdiani Suhaili; Hansen Nasif; Yelly Oktavia Sari (Universitas Airlangga, 2024)
Background: The writing of Integrated Patient Progress Notes (IPPNs) by pharmacists generally does not fulfil the correct writing standards. Objective: This study aimed to analyze the effect of education on the level of knowledge and writing profile of IPPN. Methods: A prospective analytic method research design was used with data collection techniques through questionnaires and total sampling for IPPN data. The researcher developed a valid and reliable questionnaire to measure pharmacists' level of knowledge. Education was conducted through